Impact of Obesity on Female Reproductive Hormones and Ovulatory Function. A Clinical and Biochemical Evaluation of Endocrine Disruption in Women of Reproductive Age - Hanana Hameed, Sajjad Ul Hasan, Muhammad Naveed Najeeb, Maha Sajjad, Sajida Imran, Abdul Wadood Shah, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Obesity is a global health concern that significantly affects female reproductive health. It is strongly associated with hormonal imbalances and ovulatory dysfunction, which may compromise fertility. The present study clinically and biochemically evaluates the impact of obesity on female reproductive hormones and ovulatory patterns in women of reproductive age. Objective: To assess the endocrine disruption and ovulatory dysfunction associated with obesity in reproductive-aged women through clinical and biochemical evaluation. Methodology: This cross-sectional clinical study was conducted over six months (January–June 2023) at the Department of Gynecology and Reproductive Endocrinology, Bolan Medical University Hospital, Quetta, and Mayo Hospital, Lahore, Pakistan. A total of 100 women aged 20 to 45 years were enrolled and categorized into obese (BMI ≥30 kg/m²) and non-obese (BMI <30 kg/m²) groups. Clinical data regarding menstrual regularity, ovulation history, and signs of hyperandrogenism were recorded. Biochemical parameters including serum luteinizing hormone (LH), follicle-stimulating hormone (FSH), estradiol (E2), progesterone, total testosterone, fasting insulin, and glucose were measured during the early follicular phase. Ovulatory function was evaluated using mid-luteal serum progesterone levels. Results: Obese women showed a significantly higher incidence of menstrual irregularities and anovulation compared to non-obese women (p<0.05). Serum LH/FSH ratio and total testosterone levels were significantly elevated, while mid-luteal progesterone levels were reduced in obese participants (p<0.01). A strong correlation was observed between increased BMI and insulin resistance markers, suggesting an interplay between metabolic and reproductive hormonal disturbances. Conclusion: Obesity in reproductive-aged women is strongly associated with endocrine disruption, particularly involving altered gonadotropin ratios, hyperandrogenism, and ovulatory dysfunction. These findings underscore the need for early screening and weight management strategies to restore reproductive hormonal balance and improve fertility outcomes in obese women. Keywords: Obesity, Female Reproductive Hormones, Ovulatory Dysfunction, Endocrine Disruption, Infertility, BMI, Hyperandrogenism, Insulin Resistance.